Physical Incompatibility between Vancomycin and Viscoelastic Mimicking Acute Endophthalmitis: The First Report - Biljana Kuzmanović Elabjer; Dean Šarić; Mladen Bušić; Mirjana Bjeloš; Andrej Pleše (Case Reports in Ophthalmological Medicine)
This is the first documentation of vancomycin precipitation with viscoelastic in the anterior chamber of the eye. A 34-year-old white male underwent uneventful penetrating keratoplasty. Intracameral instillation of 1 mg/0.1 mL of vancomycin followed no attempts of meticulous viscoelastic irrigation. Six hours later thick white material in the anterior chamber was sedimented. The following criteria excluded the diagnosis of endophthalmitis and TASS: clear and transparent anterior chamber and vitreous body, the absence of ciliary injection and corneal oedema, and unremarkable laboratory tests’ results. This iatrogenic complication mimicking endophthalmitis does not require any specific management and should be acknowledged in guidelines for prevention and treatment of endophthalmitis. The objective of this paper is to alert colleagues to this iatrogenic complication of vancomycin mimicking endophthalmitis. Whether this condition should be labelled as positive or negative demands further investigation. As vancomycin is a time-dependent antibiotic, it is possible that this precipitate could serve as a slowly releasing drug depot and viscoelastic as a vehicle for precipitation. This being the case, investigation is needed to analyse its potential to precipitate with another dispersive and cohesive viscoelasticity.